The Influence Of Brand Image, Perceived Quality & Price On Purchasing Decisions For Dunkin Donuts Products In Bekasi - Sukron; Hartelina Hartelina; Dede Jajang Suyaman (Enrichment : Journal of Management, 2022)
Purchasing decisions are in the stage of the buyer decision-making process in which consumers actually buy. Some of the factors that influence consumer purchase decisions are brand image, product quality and price.There has been a decline in sales in March and in April that caused the decline in the number of customers who buy products Dunkin Donuts The decline is due to the emergence of new competitors that produce similar products so that some consumers switch to a competing product. This study aimed to determine the effect of brand image, product quality and price on consumer purchasing decisions in Dunkin Donuts Bekasi. This study used a sample of 100 respondents drawn through slovin method. The data analysis technique used is the multiple regression analysis previously tested with classical assumption. The results showed that simultaneous brand image, product quality and price significantly influence consumer purchasing decisions. Partially brand image and product quality are significantly influence consumer purchase decisions and price variable is not significant influence on consumer purchasing decisions. Product quality and brand image has contributed greatly to the consumer purchasing decisions, then the parties should consider factors Dunkin Donuts product quality and brand image in company.